The Indian middle classes - Misra, B.B. (Delhi, 1978)
This study is intended to be merely an introductory survey of the Indian middle classes, a subject that remains virtually unexplored. From its very nature it is limited in scope and sketchy in treatment. Even so, it is significant in that it brings out some of the peculiar features which distinguished the Indian middle classes from their Western counterparts. In the West, especially in England, for example, the middle classes emerged basically as a result of economic and technological change; they were for the most part engaged in trade and industry. In India, on the contrary, they emerged more in consequence of changes in the system of law and public administration than in economic development, and they mainly belonged to the learned professions. India's traditional emphasis on literary education combined with Britain's rule and her imperialist economy to make the intelligentsia the dominant strand in the composition of the Indian middle classes.
Keywords: Social Classes